The Practices and Obstacles of English Language Teaching in Intellectual Disability Classroom: A Case Study at Special School (SLB) in Palembang - Dalilan; Eka Sartika; Deyana Indah Lestari (Institut Agama Islam Negeri Madura, 2021)
Individuals with disabilities learn with difficulties such as physical, emotional, mental, and social deficiencies. In a limited physical and mental condition, they are faced with problems in learning, particularly in learning English. This study aims at revealing practices and obstacles in learning English in an intellectual disability classroom that affected the teaching practices. A case study method was used in this study. This study's participants were two teachers at SLB-C Tuna Grahita Palembang selected by a typical sampling technique. The observation and interview were used to collect data regarding realized practices and obstacles in teaching English to students with intellectual disabilities. Data were analyzed using thematic analysis. The study results indicated that English language teaching practices in intellectual disability classrooms were similar to the regular ones but more oriented to students' needs. The obstacles of English language teaching were affected by intellectual disability students' limitations in writing, reading, speaking, listening skills, and heterogeneous ability.